Cognitive Counselling Effectiveness: Assertive Approach to Deal with Stereotype and Prejudice in Early Childhood - Mubiar Agustin; Heny Djoehaeni; Asep Deni Gustiana; Ryan Dwi Puspita; Yoga Adi Pratama (STAI Hubbulwathan Duri, 2025)
Hateful behavior, driven by stereotypes and prejudice related to ethnicity, gender, religion, politics, aggression, and sexuality, frequently manifests in educational settings. Addressing these issues in early childhood is crucial to fostering inclusive environments. This study employed a quasi-experimental design to evaluate the effectiveness of a Cognitive Behavioral Therapy (CBT)-assertive training intervention in reducing stereotypes and prejudice in early childhood education. Seventy children were sampled, with 20 children each assigned to an experimental and a control group. The findings reveal that children, even at a young age, exhibit stereotyped behaviors of low intensity, and some demonstrate prejudice. The CBT-assertive training intervention significantly reduced these behaviors in the experimental group. Notable outcomes included a marked decrease in stereotyped behaviors and a positive shift in attitudes among children who participated in the training. These results suggest that CBT-assertive training is an effective method for reducing stereotypes and prejudice in early childhood education. Incorporating this approach into early education curricula has the potential to promote social and emotional well-being. CBT-assertive training holds promise as a practical strategy for fostering inclusivity and addressing bias in early childhood. Future research should examine the long-term impact and broader applicability of this intervention in diverse educational settings.